The rules of capacity in the civil codification and family codification, from the hypothesis of complementarity between the texts to the reality of conflicting rulings - CHIHANI, Samir; GATTAL, Hamza (Journal of Human Sciences, 2025)
It is known that the civil codification is the general Shariah, reffering to it whenever there is no text on a specific issue in the rest of the relevant laws. Among these laws; the codification of the family. The civil codification included general provisions regarding capacity rules, some of them reffered to the texts of the family codification which had not yet been issued, and this embodies in the phenomenon of the principle of complementarity between the two laws. However, the issuance of the family codification nine years after the issuance of the civil codification showed the converse in many placements. Particularly in the rules governing the capacity of persons; therefore, the purpose of this study was to analyze the content of those rules, with shedding light the areas of incompatibility between them, and then providing solutions to get out of the state of incoherency between texts or even conflict between them.